2005
DOI: 10.1016/j.cattod.2005.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II)-catalyzed enhancement of ultrasonic-induced degradation of diethylstilbestrol (DES)

Abstract: The oxidation of the endocrine disruptor, diethylstilbestrol (DES) in aqueous media by ultrasound is significantly enhanced by Fe(II) catalyst. The observed enhancement is likely the result of increased levels of hydroxyl radicals from the iron-promoted reduction of the hydrogen peroxide produced during ultrasonic irradiation. The degradation is effective over a range of concentrations and is consistent with pseudo first-order kinetics. Relatively high concentrations of hydrogen peroxide, $450 mM, are present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…During aque- ous ultrasonic irradiation, water can be subjected to pyrolysis and generates hydroxyl radicals. The catalysis of Fe(II) in ultrasound system was confirmed by Abderrazik et al [25] and Nam et al [26]. It was reported that the partial recombination of hydroxyl radicals would result in the formation of hydrogen peroxide (H 2 O 2 ) in ultrasound system, and the H 2 O 2 production decreased by the addition of Fe(II), due to the reaction of Fe(II) with H 2 O 2 (Fenton's reaction).…”
Section: Effect Of Fe(ii) As a Catalystmentioning
confidence: 79%
“…During aque- ous ultrasonic irradiation, water can be subjected to pyrolysis and generates hydroxyl radicals. The catalysis of Fe(II) in ultrasound system was confirmed by Abderrazik et al [25] and Nam et al [26]. It was reported that the partial recombination of hydroxyl radicals would result in the formation of hydrogen peroxide (H 2 O 2 ) in ultrasound system, and the H 2 O 2 production decreased by the addition of Fe(II), due to the reaction of Fe(II) with H 2 O 2 (Fenton's reaction).…”
Section: Effect Of Fe(ii) As a Catalystmentioning
confidence: 79%
“…The promising results have been reported when the coupling of Fenton's reagent with ultrasonic irradiation (named sono-Fenton process) was used to the decomposition of chlorinated aromatic * Corresponding author. hydrocarbons [5], endocrine disruptors [6,7], anionic surfactants [8], 2,4-dinitrophenol [9], EDTA [10], MTBE [11], and dyes [12,13]. Like classical Fenton process, the use of homogeneous iron catalysts leads to the ferric hydroxide sludge during neutralization stage of sono-Fenton process, which requires additional separation and disposal [3].…”
Section: Introductionmentioning
confidence: 98%
“…AOPs that had been developed to degrade DES, included ultrasonic-induced degradation, electrochemical degradation, photooxidation degradation, UV-light-inducing photodegradation, and ozonation (Abderrazik et al 2005;Korshin et al 2006;Lin et al 2009;You et al 2006;Zhou et al 2004). Although these methods could effectively remove DES from the environments, the whole processes needed specific cells in site, such as cells with ultrasound sample, PbO 2 anode, and stainless steel cathode, or certain equipment including highpressure mercury lamp and ozone generator.…”
Section: Introductionmentioning
confidence: 99%